Using gamification techniques in digital sports marketing - Skorokhodov S.N. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to develop algorithms for the effective use of digital gamification tools in the marketing strategies of sports organizations. Methods and structure of the study. The following scientific methods were used in the course of the work: the method of system analysis, the method of comparative characteristics, generalization, systematization, structural and functional method. Results and conclusions. A reasonable conclusion is made that the effectiveness and efficiency of competitive marketing strategies in sports is determined by the degree of integration of elements of innovative, creative interaction of organizations with the target audience. The involvement of fans and consumers of sporting goods and services in marketing communications through gamification tools provides conditions for long-term cooperation and, consequently, strengthening the company’s image and brand in the external environment of sports marketing. Gamification as a set of effective ways and methods of interactive digital marketing finds successful application in various segments of the sports industry, optimizing the solution of operational tasks related primarily to employee motivation and training, multi-channel customer engagement, as well as improving marketing results in the context of long-term strategic decisions. By means of such innovative solutions, not only the competitive advantages of individual business entities are formed, but also the investment attractiveness of the sports industry as a whole is increased.